Rising consumption of meat and milk in developing countries has created a new food revolution - Delgado, Christopher L. (2003)
People in developing countries currently consume on average one-third the meat and one-quarter of the milk products per capita compared to the richer North, but this is changing rapidly. The amount of meat consumed in developing countries over the past has grown three times as much as it did in the developed countries. The Livestock Revolution is primarily driven by demand. Poor people everywhere are eating more animal products as their incomes rise above poverty level and as they become urbanized. By 2020, the share of developing countries in total world meat consumption will expand from 52% currently to 63%. By 2020, developing countries will consume 107 million metric tons (mmt) more meat and 177 mmt more milk than they did in 1996/1998, dwarfing developed-country increases of 19 mmt for meat and 32 mmt for milk. The projected increase in livestock production will require annual feed consumption of cereals to rise by nearly 300 mmt by 2020. Nonetheless, the inflation-adjusted prices of livestock and feed commodities are expected to fall marginally by 2020, compared to precipitous declines in the past 20 y. Structural change in the diets of billions of people is a primal force not easily reversed by governments. The incomes and nutrition of millions of rural poor in developing countries are improving. Yet in many cases these dietary changes also create serious environmental and health problems that require active policy involvement to prevent irreversible consequences.